1993
DOI: 10.1128/mcb.13.6.3202
|View full text |Cite
|
Sign up to set email alerts
|

Cis- and trans-acting elements involved in amino acid regulation of asparagine synthetase gene expression.

Abstract: We have previously shown that asparagine synthetase (AS) mRNA expression can be dramatically upregulated by asparagine deprivation in tsll cells, mutants of BHK hamster cells which encode a temperaturesensitive AS. The expression of AS mRNA was also induced upon starvation for one of several essential amino acids in HeLa cells. We also showed that regulation of AS mRNA expression by amino acid concentration has both transcriptional and posttranscriptional components. Here we report the analysis of the elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 32 publications
3
77
1
Order By: Relevance
“…Promoter analysis studies employing a luciferase reporter assay identified a region that responded to all dipeptides tested and also to selected amino acids, such as Lys, Arg, and especially Phe. This region comprises 254 bp and contains an amino acid response-like element as found in the asparagine synthetase gene (32). Rat and mouse Pept1 and the murine Pept2 promoter regions contain these amino acid response-like elements with a bp substitution in the fifth bp (25,52).…”
Section: Regulation Of Expression Level and Transport Activity Of Pepmentioning
confidence: 99%
“…Promoter analysis studies employing a luciferase reporter assay identified a region that responded to all dipeptides tested and also to selected amino acids, such as Lys, Arg, and especially Phe. This region comprises 254 bp and contains an amino acid response-like element as found in the asparagine synthetase gene (32). Rat and mouse Pept1 and the murine Pept2 promoter regions contain these amino acid response-like elements with a bp substitution in the fifth bp (25,52).…”
Section: Regulation Of Expression Level and Transport Activity Of Pepmentioning
confidence: 99%
“…Indeed the AS promoter sequence on the bottom strand (nt Ϫ57 to Ϫ75) revealed a high identity to the CHOP AARE on the top strand (nt Ϫ313 to Ϫ295), not only in the AARE core, but also in both of the border sequences. By nucleotide substitutions, this AS sequence had been shown by independent laboratories to be important for the response to amino acid starvation (8,9). Furthermore, previous studies had shown that the CHOP AARE-like NSRE-1 sequence is not The minimum core consensus sequence is represented.…”
Section: The Nucleotides Required In the Chop Aare Core Sequence To Mmentioning
confidence: 99%
“…The level of AS mRNA increases in response not only to asparagine starvation, but also to deprivation of any individual essential amino acid (5-7). Guerrini et al (8) used promoter deletion and mutation to analyze the proximal promoter of the human AS gene. They identified the palindromic sequence 5Ј-CATGATG-3Ј at nucleotides Ϫ70 to Ϫ64 as necessary for the AS promoter regulation by amino acid availability.…”
mentioning
confidence: 99%
“…Guerrini et al (9) identified a region from nt Ϫ70 to Ϫ62 within the human A.S. promoter that functioned as an amino acid response element (AARE). More recently, Barbosa-Tessmann et al (10 -12) have demonstrated that the human A.S. gene is also induced by glucose deprivation and that this activation is mediated by the endoplasmic reticulum stress response (ERSR), also known as the unfolded protein response pathway in yeast (13).…”
mentioning
confidence: 99%
“…More recently, Barbosa-Tessmann et al (10 -12) have demonstrated that the human A.S. gene is also induced by glucose deprivation and that this activation is mediated by the endoplasmic reticulum stress response (ERSR), also known as the unfolded protein response pathway in yeast (13). In vivo footprinting and mutagenesis demonstrated that the promoter sequence 5Ј-TGATGAAAC-3Ј (nt Ϫ68 to Ϫ60), the region first identified by Guerrini et al (9), was also responsible for induction of the A.S. transcription following activation of the ERSR pathway (12). The ERSR activation demonstrates that this A.S. promoter sequence serves in a broader capacity than simply as an AARE and, to reflect this broader substrate-detecting capability, this sequence is referred to as the nutrient-sensing response element-1 (NSRE-1).…”
mentioning
confidence: 99%